Emerging Intelligent Computing Technology and Applications 5th International Conference on Intelligent Computing, ICIC 2009, Ulsan, South Korea, September 16-19, 2009. Proceedings - Huang, De-Shuang.; Jo, Kang-Hyun.; Lee, Hong-Hee.; Kang, Hee-Jun.; Bevilacqua, Vitoantonio. (Lecture Notes in Computer Science, 2009)
This book - in conjunction with the volume LNAI 5755 - constitutes the refereed proceedings of the 5th International Conference on Intelligent Computing, ICIC 2009, held in Ulsan, South Korea in September 2009. The 214 revised full papers of these two volumes were carefully reviewed and selected from a total of 1082 submissions. The papers are organized in topical sections on Supervised & Semi-supervised Learning, Machine Learning Theory and Methods, Biological and Quantum Computing, Intelligent Computing in Bioinformatics, Intelligent Computing in Computational Biology and Drug Design, Computational Genomics and Proteomics, Intelligent Computing in Signal Processing, Intelligent Computing in Pattern Recognition, Intelligent Computing in Image Processing, Intelligent Computing in Communication and Computer Networks, Intelligent Computing in Robotics, Intelligent Computing in Computer Vision, Intelligent Agent and Web Applications, Intelligent Sensor Networks, Intelligent Fault Diagnosis & Financial Engineering, Intelligent Control and Automation, Intelligent Data Fusion and Security, Intelligent Prediction & Time Series Analysis, Natural Language Processing and Expert Systems, Intelligent Image/Document Retrievals, Computational Analysis and Data Mining in Biological Systems, Knowledge-Based Systems and Intelligent Computing in Medical Imaging, Applications of Intelligent Computing in Information Assurance & Security, Computational Analysis and Applications in Biomedical System, Intelligent Computing Algorithms in Banking and Finance, and Network-Based Intelligent Technologies.